Effects of Red-Fleshed Pitaya (Selenicereus polyrhizus) Ingestion after Strenuous Exercise on Creatine Kinase and Mitochondrial Function in Rat Muscle Cells - Rusip, Gusbakti; Ilyas, Syafrudin; Lister, I Nyoman; Ginting, Chrismis Novalinda; Mukti, Ade Indra; Girsang, Ermi (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Free radicals formed during strenuous exercise through an increase in reactive oxygen species induce damage to tissues (e.g., muscle and liver) and cause oxidative damage to cells, resulting in mitochondrial dysfunction. AIM: As an effective method to repair mitochondrial muscle cell function, this study investigated the effects of red-fleshed pitaya (RFP) ingestion on creatine kinase (CK), which is a biomarker for muscle tissue damage, and malondialdehyde (MDA) levels during strenuous exercise. METHODS: This study involved 25 3-month-old male rats with an average weight of 200 g. The RFP extract was obtained through ethanol extraction and concentrated using an air-drying method. Rats were randomly allocated into five groups as follows: Two control groups (K1 [no-exercise, no RFP] and K2 [exercise, no RFP]) and three test groups (P1, P2, and P3; subjected to exercise and treated with 75, 150, and 300 mg kg−1 body weight of RFP, respectively). The exercise was in the form of swimming for 20 min 3 times/week for 31 days. CK and MDA were measured through an enzyme-linked immunosorbent assay, and histopathological examinations were performed through hematoxylin and eosin staining of rat muscles. RESULTS: The MDA levels after the ingestion of RFP extracts were compared between the K2 group and the P1, P2, and P3 groups. The results showed significant differences (p < 0.05 for P1 and P2, and p < 0.01 for P3), indicating the production of free radicals and CK, with features of damaged muscle cells based on histopathology. Ingestion of the RFP extract led to improvements in soleus muscle cells, resulting in cell function repair. CONCLUSION: Levels of MDA and CK increased during exercise, which caused significant muscle damage. However, after treatment with the RFP extract, the levels of both markers decreased. Thus, strenuous exercise causes an increase in reactive oxygen species, resulting in increased free radical levels. RFP ingestion decreased oxidative stress levels, thus repairing mitochondrial cell function.